Insights Into Cancer Awareness and Health Practices in Rural Kenya: A Cross-Sectional Study of Esophageal, Breast, Prostate, Cervical, and Colorectal Cancers - Rosebella Iseme-Ondiek; Joseph Abuodha; Anthony Ngugi; Innocent Abayo; Mansoor Saleh (JCO Global Oncology)
PURPOSEIn sub-Saharan Africa (SSA), there has been an epidemiologic transition from infectious diseases to noncommunicable diseases, including a projected doubling in incidence of cancer. Understanding the underlying factors driving this surge is crucial for designing effective strategies to mitigate the cancer burden. This study focuses on assessing knowledge, attitudes, screening practices, and health behaviors related to five most prevalent cancers in SSA: prostate, breast, cervical, esophageal, and colorectal—among a predominantly rural coastal population in Kenya.MATERIALS AND METHODSWe used a cross-sectional study design targeting 1,500 adult respondents randomly selected from an existing community health and demographic surveillance system. Face-to-face interviewer-administered questionnaires were used to collect data.RESULTSOne thousand four hundred fifty-two adults participated in the final survey. Breast cancer awareness was highest (69.1%), while awareness of colorectal cancer was lowest (34.6%). Given a list of possible risk factors and symptoms, most respondents (>50%) could only recognize one to two per cancer type. Perceptions of survival from colorectal cancer were particularly pessimistic, with <70% recognizing early detection as a means to improve survival outcomes. In terms of cancer-associated risk factors, more men engaged in tobacco and alcohol use (20.5% and 22.4%, respectively). Additionally, fewer than 10% of eligible participants had ever undergone cancer screening.CONCLUSIONThis study addresses a gap in population-level Knowledge, Attitudes, and Practices studies in rural SSA, offering insights crucial for cancer prevention, early detection, and treatment. The low awareness and knowledge levels and unhealthy behaviors emphasize a need for targeted educational campaigns at community level and enhanced understanding of barriers to uptake of screening if we are to effectively combat the growing cancer burden in this region.